Ulcerative form of pyoderma gangrenosum (a case study description) - A. V. Patrushev; A. V. Samtsov; V. V. Barbinov; A. V. Sukharev; I. E. Belousova; A. . S Chizhov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The authors describe a case of pyoderma gangrenosum when the patient's external therapy included Tecasorb disposable sterile tissue-based absorption wipes featuring activated carbon manufactured based on nanotechnologies. The authors describe and confirm that the following present-day study method can be used for diagnostics of the disease: mass spectrometry of microbial agents in biological environments.